(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify the Generating solutions for the physically disabled according to gender. To identify the prevailing identity styles among the physically disabled in terms of gender. To identify the relationship between generating solutions and identity styles for people with mobility disabilities. To identify the extent to which identity methods contribute to generating solutions for the physically disabled. The research sample consisted of 200 male and female students with physical disabilities who are present in the Al-Saada and Al-Manar institutes in Baghdad, Rusafa II, and III for the academic year 2022-2023. The researcher developed two research tools (generating solutions and identity methods), where the researcher developed a scale for generating solutions according to Sternberg’s theory (1995), The number of items in the scale was 40, distributed over four domains (solutions to social problems, solutions to health problems, solutions to family problems, and solutions to academic problems). Each domain takes 10 items. As for the identity styles scale, it was constructed according to Berzonsky’s theory (1989). The number of items in the scale was 40, with four alternatives (always, sometimes, rarely, never) distributed over four identity styles (the standard style, the informational style, the dispersed style, and commitment to identity). Each style takes 10 items. The researcher used one sample t-test, two samples t-test, and independent and regression analysis. The results revealed that generating family and school solutions is the most common among people with mobility disabilities. There are no statistically significant differences between males and females with physical disabilities in generating solutions. The prevailing identity style among the physically disabled is the standard style. There are no statistically significant differences between males and females with physical disabilities in identity styles. There is a relationship between generating solutions and identity styles, partly between the normative, informational, and dispersed styles (identity styles) and social and family solutions (generating solutions), and there is no connection between the commitment style and solutions. The result also shows that the percentage contribution of identity methods in generating solutions is as follows: The informational identity method contributes to generating social solutions by 56% and family solutions by 27%. The standard identity style contributes to generating social solutions by 44% and family solutions by 28%. The dispersed identity style contributes to generating social solutions by 73% and family solutions by 34%. As revealed from the analysis of variance test, we find that the F values for the identity styles (informational, cognitive, and dispersed) and the solutions (social and family) are all statistically significant.